Accelerating the electrochemical kinetics of Na3V2(PO4)3 cathode for high-performance sodium ion batteries with superior cycling stability by Cl− substitution - Wang, Jiancang; Lai, Xueqi; Li, Zheng-Xiao; Wang, Pengfei; Zhang, Jun-Hong; Yi, Ting-Feng (Journal of industrial and engineering chemistry (Seoul, Korea), 2024)
Na3V2(PO4)3 (NVP) has been recognized as one of most prospective cathode materials of sodium-ion batteries(SIBs) due to its excellent thermal stability and high voltage plateau. Nevertheless, its inherent poor electronicconductivity limits its further large-scale applications. Herein, we propose an efficient strategy to improveelectrochemical kinetics of Na3V2(PO4)3 cathode by Cl doping. The incorporation of Cl effectively enhances theelectronic transport pathways within the NVP material. Additionally, it introduces supplementary charge carriers,thereby modulating the internal charge balance of the crystal lattice and mitigating electron confinement. Although the as-prepared Na3V2(PO4)2.8Cl0.6 and pristine NVP material show similar discharge capacity at lowrate (0.1C), the former delivers higher capacity at high rates (0.2, 0.5, 1, 2, 5, 10, and 20C), indicating excellentrate performance. Notably, even after 2000 cycles at 10C, Na3V2(PO4)2.8Cl0.6 maintains a capacity retention ofapproximately 70 %. Remarkably, it retains 63 % of its initial capacity (48.1 mAh/g) after 5000 cycles at thedemanding 20C, with a Coulombic efficiency approaching 100 %. These findings underscore the efficacy of Cldoping as a means to enhance the electrochemical properties of NVP, providing valuable insights into thedesigning of high-performance SIBs cathode materials. KCI Citation Count: 0